Dataset: Census of individual trees of Tucunare Vichada (2020) - Ruiz-Hurtado, Andres Felipe; Pérez Bolaños, Juliana; Arrechea-Castillo, Darwin Alexis; Matiz Rubio, Natalia; Costa Junior, Ciniro; Arango Mejia, Jacobo; Cardoso Arango, Juan Andres (2024)
This dataset contains information of individual trees in Tucunare, Vichada-Colombia extracted from remote sensing imagery processed using AI models. Information from the High Resolution 1-meter Global Canopy Heights map from Meta-AI. The dataset includes a CSV file containing attributes related to tree dimensions and geolocation and a shapefile with polygons representing each tree